Halal label: interreligious youth's consumption decisions regarding Korean products - Susilowati, Eri; Lumban Toruan, Ningsih Sepniar (Journal of Halal Product and Research (JHPR), 2024)
As a pluralistic society, Indonesian consumers have various purchasing decisions from religious values to the virality of the product in online space. The products available in the market are not solely produced in Indonesia but also imported from global markets, including South Korea. Aligned with the globalized market, the Korean wave in Indonesia is a significant phenomenon influencing consumer buying decisions. This paper aims to examine how Indonesian youth from different religious backgrounds perceive and make consumption decisions regarding imported Korean products labeled as halal. Moreover, to what extent halal narratives product review affects consumer behavior. This research utilizing qualitative methods conducted interviews with Indonesian youth K-Pop fans from different religions and the findings will be applied through thick description analysis. The research reveals a broad decision making among consumers towards halal products associated with South Korea. Additionally, social media influencers who review the products play a role in their purchasing decisions. Keywords: Halal Awareness, Halal Certification, Korean Wave, Korean Food, Purchasing Decision